A Legal and Policy Argument for Bail Denial and Preventative Treatment for Batterers in the United States. (May 2017) - Beichner, Dawn; Ogle, Robbin; Garner, Anne; Anderson, Daniel
Historically, battering has been a culturally and legally acceptable form of social control within the United States. This article provides an examination of how this legacy of social acceptance has influenced the development of laws and social policies related to battering. We provide a critique of our current approach to battering and our historical reliance on private or social helping agencies intended to hide and protect victims. We call for a transformation of our current policies that provides for the removal of the batterer—not the victim and her children—from the family home through a process of bail denial and preventative detention.